"A Different Kind of Theo-Politics: Abraham Joshua Heschel, the Prophets and the Civil Rights Movement". Issue 1 (17th February 2020) - Heschel, Susannah
ABSTRACT: This paper explores the sharp differences in the understanding of the Hebrew prophets by theologians, Jewish and Protestant, in Germany and the United States, with a particular focus on their invocation of prophetic teachings in relation to social and political movements. The sharp denigrations of the prophets – described as ecstatics (Gunkel) or rural naifs (Troeltsch) rendered the prophets useless as figures of inspiration in Germany in relation to racism, colonialism, and WWI. By contrast, the prophets have played a crucial role in American civil thought, especially in the Civil Rights Movement. The distinctive and influential interpretation of prophetic consciousness developed by the German-American Jewish theologian Abraham Joshua Heschel is examined for its parallels with the prophetic theology of Martin Luther King, Jr., and the political ramifications of Heschel's link between prophetic revelation and political leadership.